Amelioration of Ultrasonic Transducer to Study CuO Doped Thin Films - Mirham Abdallah Youssef BARAKAT (Archives of Acoustics)
Ultrasonic pulse echo technique was used to study cupric oxide (CuO) thin films. CuO thin films were prepared using sol gel technique. They were doped with Lithium (Li) (1%, 2% and 4%).